EDITORIAL - Sayyid M. Syeed (International Institute of Islamic Thought, 1994)
This is the last issue of AJISS that I have planned and edited. I have been associated with this journal since we named it AJISS and coined the term "Islamic social science." These years have been characterized by a great struggle to define and to develop Islamic social sciences and to identify scholam both here and abroad who were willing and qualified to work for the intellectual reform of the ummah. Being involved in a movement during its formative period is a great challenge. Now that AJISS has been produced for ten yeam, the vision of Islamic social sciences is much clearer, the potential writers have been identified, prominent scholars in the related fields have been drawn into the debate, and many young wseamhers are taking a cue for their future projects from the issues raised in AJISS. We are greatful to Almighty Allah for granting us success in this mission and hope that the journal will continue to provide a healthy forum for intellectual dialogue. Once again I have been called upon to take up a new challenge. After a decade of mobilizing Muslim intellectuals and involving both Muslim and non- Muslim scholars in a debate about the relevance of Islam to contemporary life, I will be dedicating more of my energies to developing an Islamic vision for North America in my new role as Secretary General of the Islamic Society of North America (ISNA). The Islamic Society of Notth America grew out of the former Muslim Students Association of the United States and Canada (MSA). This latter organization was born and brought up in university campuses and thus has a rich intellectual tradition and a great inhetent potential. The Association of Muslim Social Scientists (AMSS), the ccqxmsor of AJISS, is one of the affiliates of ISNA, as is the MSA. This makes the pool of Muslim social scientists and students available to ISNA for developing its plans and programs based on an informed analysis and a sound methodology. In the United States, we are engaged in community formation and the establishment of Islamic educational, economic, social, and other institutions. Muslims are playing a positive and historic role in making Islam undetstood and relevant through their contributions and presence. The ...